Carcharhinus falciformis - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
Carcharhinus falciformis (Müller & Henle, 1839) – Silky shark; Tubarão-luzidio ① , ②③ The occurrence of this species off Madeira needs confirmation (Wirtz et al. 2008). Ebert & Stehmann (2013) indicated its presence off Madeira, based on known geographical distribution. Arruda (1997) considered the presence of C. falciformis off the Azores doubtful : Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 11, DOI: 10.5852/ejt.2014.73, http://zenodo.org/record/3866515 : {"references": ["Wirtz P., Fricke R. & Biscoito M. J. 2008. The coastal fishes of Madeira Island - new records and an annotated check-list. Zootaxa 1715: 1 - 26.", "Ebert D. A. & Stehmann M. F. W. 2013. Sharks, batoids, and chimaeras of the North Atlantic. FAO Species Catalogue for Fishery Purposes no. 7, Food and Agriculture Organization, Rome.", "Arruda L. M. 1997. Checklist of the marine fishes of the Azores. Arquivos do Museu Bocage, Nova Serie 3 (2): 3 - 164."]}